Intellectual Capital and Corporate Social Responsibility in Banking Industries in Indonesia - Dri Asmawanti S; Indah Oktari Wijayanti (Journal of Economics, Business, and Accountancy Ventura, 2017)
This study aimed to get empirical evidence on the relationship of the intellectual capital of the company with its corporate social responsibility. The data used in this study were the banking industry companies listed on the Indonesia Stock Exchange. The sample in this study was banking company in Indonesia which has been qualified sampling. The analysis tool to test the hypothesis was multiple regression analysis using SPSS. The results of this study showed that the disclosure of intellectual capital significantly influenced social responsibility. In addition to the control variables of this study, the performance of the company had an influence on social responsibility. This is because of the human resources owned by a company would be able to work optimally with the support of enterprise systems is good, the good quality system and strong customer capital. The implication of research is company's performance especially on social responsibility, which is the most investors in Indonesia are still oriented on profit, the greater the profit that has the company cares about the environment.